IMPROVEMENT IN CONCEPTION RATE BY GnRH OR hCG ADMINISTRATION ON DAY 5 POST-AI IN NON-INFECTIOUS REPEAT BREEDER COWS - ANBHULE, R S; SAWALE, A G; MARKANDEYA, N M; KUMAWAT, B L; KADAM, P D; LAWANGE, S R (The Indian Journal of Animal Reproduction, 2022)
Thirty-six non-infectious repeat breeder cows were selected on the basis of typical fern pattern, negative whiteside test, normal pH of cervical mucus and
Keywords: Conception rate; GnRH; hCG; Non-infectious; Repeat breeder